Business Policy and Competitiveness of Farmers’ Organizations—Empirical Evidence from Taiwan - Shu-Yi Chi; Tsorng-Chyi Hwang; Li-Hsien Chien (Agriculture, 2023)
Sustainable competitiveness is at the core of effective organizational management. However, the interpretation of the concept of competitiveness is quite divided, especially for organizations that are positioned as social enterprises and must bear profits and losses. In this context, we used the PLS-SEM method to discuss the impact of business policies on organizational resource management and select the Taiwanese farmers’ associations for analysis. According to the resource-dependent model, we selected the corresponding variables from the existing operational competition indicators to represent the four major business sectors of these associations. The main contribution of this study is that through expert opinion, the evaluation indicators of the existing business performance competition can be integrated to define the competitiveness of farmers’ associations. We also used the fuzzy C-means method cluster analysis to effectively divide 279 farmers’ associations into six groups according to “population, land, and industry”. It is possible to evaluate the competitiveness of the departments and business policies of the farmers’ associations in different groups according to the performance of their departments. Presenting the differences in business policies will help the government implement effective counseling services between regions. Competitiveness based on the performance of the main functions significantly affects the business execution, asset allocation, marketing, and sales activities of the farmers’ associations. This article clearly points out that an organization may achieve a competitive business objective by taking stock of its own operating and financial conditions. This is also true for non-profit social enterprises.